Coaching Clinic on Community Service Proposal Development: An Approach to Increasing Grant Acceptance Success in Higher Education Institutions - Vicky Dzaky Cahaya Putra; Titta Hartyana Sutarna; Amanda Aprilia Dwisanny; Deny A. Sopiyadin (Research Collaboration Community (Rescollacom), 2026)
This study aims to analyze the effectiveness of coaching clinic activities in improving proposal quality and increasing the success rate of community service grant acceptance within higher education institutions. A qualitative approach with a descriptive-analytical design was employed. Data were collected through observations, documentation of proposals before and after the coaching clinic activities, and evaluations conducted by internal reviewers. Data analysis was carried out using content analysis techniques, with key indicators including the clarity of problem formulation, the relevance of research-based solutions, the level of innovation, the feasibility of outputs, and budget appropriateness. The results indicate that the coaching clinic had a significant impact on improving proposal quality and faculty participation. An increase in the number of submitted proposals was recorded, with 12 proposals successfully approved and 12 proposals passing the review stage, although several proposals remained in the draft phase. The intensive mentoring model based on continuous feedback, supported by an internal quality assurance mechanism, emerged as a key success factor. The novelty of this study lies in the implementation of a structured and sustainable coaching clinic model, which differs from conventional one-way training approaches. Therefore, strengthening assistance during the proposal finalization stage and developing a timeline-based monitoring system are recommended to ensure sustainability and optimize outcomes.